2019
DOI: 10.1038/s41598-019-46453-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutritional stress on the honeybee colony health

Abstract: Honeybees Apis mellifera are important pollinators of wild plants and commercial crops. For more than a decade, high percentages of honeybee colony losses have been reported worldwide. Nutritional stress due to habitat depletion, infection by different pests and pathogens and pesticide exposure has been proposed as the major causes. In this study we analyzed how nutritional stress affects colony strength and health. Two groups of colonies were set in a Eucalyptus grandis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 77 publications
0
62
0
2
Order By: Relevance
“…For example, peaks of IAPV prevalence were observed from early spring (February-April) to early summer (June-July) depending on the year [131]. Such temporal dynamics of incidence of infectious diseases are a common phenomenon, generally attributed to variations in environmental factors (e.g., temperature and daylight in temperate regions) and the subsequent changes in resource availability affecting host behavior, density, brood production and possibly host immune competence to fight pathogen infections [132][133][134][135][136].…”
Section: Temporal Dynamics Of Viruses Infecting Honey Beesmentioning
confidence: 99%
“…For example, peaks of IAPV prevalence were observed from early spring (February-April) to early summer (June-July) depending on the year [131]. Such temporal dynamics of incidence of infectious diseases are a common phenomenon, generally attributed to variations in environmental factors (e.g., temperature and daylight in temperate regions) and the subsequent changes in resource availability affecting host behavior, density, brood production and possibly host immune competence to fight pathogen infections [132][133][134][135][136].…”
Section: Temporal Dynamics Of Viruses Infecting Honey Beesmentioning
confidence: 99%
“…They find that the performance of honey bee colonies (adult bee mass and brood) and biomarkers associated with adequate nutrition (e.g., vitellogenin) are positively influenced by their foraging proximity to CRP lands. In straight relationship with the work described above, Branchiccela et al [98] recently demonstrated that the nutritional state is related to the variety of pollen in the bees’ diet, and has a severe impact on bee colony strength and health, with both short and long-term consequences.…”
Section: Nutrition and Immunitymentioning
confidence: 79%
“…Besides, pollen activates nutrient-sensing and metabolic pathways, and influences the expression of genes involved in longevity, immune function, the production of certain antimicrobial peptides and pesticide detoxification [42,103]. At the same time, it is important to take into consideration that protein sources based on pollen mixes could be contaminated with different pesticides [98].…”
Section: Nutrition and Immunitymentioning
confidence: 99%
“…2, Supplementary Table S6). Previous studies highlighted how nutritional stress shapes the gut microbiota composition [113,114] inducing long term negative impacts on honeybee health [114]. Therefore, it is very likely that higher bioaccumulated clothianidin in younger bees (with an immature microbiota) would have long-term health effect.…”
Section: Discussionmentioning
confidence: 99%